2018
DOI: 10.3904/kjim.2016.053
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin extract ameliorates murine autoimmune arthritis through regulation of TLR4/MyD88/NF-κB signaling pathway

Abstract: Background/Aims:Grape seed proanthocyanidin extract (GSPE) has been reported to have a beneficial effect on regulating inf lammation. However, the anti-inflammatory mechanism of GSPE remains unclear. The aim of this study was to verify the influence of GSPE on the Toll-like receptor 4 (TLR4)-mediated signaling pathway in the regulation of murine autoimmune arthritis.Methods:Collagen-induced arthritis (CIA) was induced in dilute brown non-agouti (DBA)/1J mice. The mice were treated with GSPE (0 or 100 mg/kg) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Supplementation of GSE remove the TD lesions, recovered the TD chicks and down-regulated the CA2 expression. Former scholars also reported the downregulation of CA2 expression in rats after the supplementation of GSE (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Supplementation of GSE remove the TD lesions, recovered the TD chicks and down-regulated the CA2 expression. Former scholars also reported the downregulation of CA2 expression in rats after the supplementation of GSE (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Grape seed is well known for its variety of antioxidative derivatives such as oligomeric proanthocyanidins and catechins, as well as anti-inflammatory potentials, is one of the most popular remedies for the treatment of OA [10,11]. Literature reported that the efficacy of grape seed extract administered orally on OA in rats led to the prevention of loss of chondrocyte cells and proteoglycan, formation of osteophytes, reducing reactive oxygen species, and inflammation mediators such as MMP13, nitrotyrosine, and IL-1β, in experimental models [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effects of procyanidins have been demonstrated to be greater than those of its isolated fractions [76,78,79]. Supported by other observations [31,32] and clinical data that have shown that procyanidins from pine bark extract reduce OA pain and inflammation [80,81], our study further suggests that, as generally recognized as safe (GRAS) biologically-active compounds, procyanidins and their active ingredients including procyanidin B2 and procyanidin B3, exert mitigating effects on OA pathogenesis. In particular, our study shows that procyanidins B2 and B3 can largely replicate the mitigating effects of procyanidins in VEGF-mediated OA pathogenesis, highly indicating that these compounds are the active ingredients in procyanidins in OA disease modification.…”
Section: Discussionmentioning
confidence: 78%
“…In animal studies, grape seed extract, rich with procyanidins, reduce ROS activity and expression of matrix metalloproteinases (MMPs) in the articular cartilage of monosodium iodoacetate-induced OA rats [30], and procyanidins extracted from grape seeds ameliorate collagen-induced arthritis (CIA) in mice through regulation of the toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor-κB (NF-κB) signaling pathway [31]. Notably, daily oral administration of procyanidin B3, one of the components of procyanidins, was shown to mitigate OA pathogenesis in mice subject to medial collateral ligament transection and medial meniscectomy by, at least in part, suppressing induced nitric oxide synthase (iNOS) [32].…”
Section: Introductionmentioning
confidence: 99%